Coronal sealing ability of three temporary filling materials - Naseri, Mandana; Ahangari, Zohreh; Moghadam, Mahyar Shahbazi; Mohammadian, Manijeh (Iranian Endodontic Journal, 2011)
Introduction: Providing adequate coronal seal of temporary filling materials is critical for the success of root canal therapy. The aim of this in vitro study was to compare coronal seal ability of three restorative materials over different periods of time. Materials and Methods: Ninety-eight molar teeth were selected. Once access cavities were prepared, teeth were divided randomly into three time groups (1 day, 1 week, and 4 weeks). Each group was then subdivided into three groups of 10 teeth. Each subgroup was restored using one of three restorative materials including Coltosol, Cavizol and Zonalin and then incubated in distilled water at 37ºC. The samples were then immersed in 2% methylene blue dye. After rinsing and drying, teeth were sectioned longitudinally and examined for dye penetration. Kruskal-Wallis and Mann Whitney U tests were used to analyze the data. Results: All experimented materials showed increasing leakage from the 1st day to the 4th week. Zonalin showed more leakage than Coltosol and Cavizol at each time interval (P<0.05), but there was no significant difference between Coltosol and Cavizol. <span style="font-style: normal; font-family: ";Times New Roman";,";serif";; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Conclusion:<span style="font-family: ";Cambria";,";serif";; color: black; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-bidi-font-family: 'Times New Roman';"> Coltosol and Cavizol are suitable temporary materials for up to 1 week.